Germinabilidade de sementes De Physalis Angulata L. (Solanaceae) sob condições de estresses abióticos - Souza, Cíntia Luiza Mascarenhas de (2009)
Many plant species have properties that can be applied in the pharmaceutical industry, cosmetics, food, among others. However, the environmental conditions under which these species grow, their resistance and tolerance to fluctuations influence on their development. The physiological behavior of the seeds should be studied so that we can better understand the physiology and mechanisms of recovery of seed germination under adverse environmental conditions, thereby establishing protocols for optimizing the germination process. The species Physalis angulata L. belongs to the Solanaceae family and shows promise in studies focused on bioprospecting, especially the production of plant hormones known as physalins. This paper describes the physiological and morphological profiles of seeds of Physalis angulata L. subjected to abiotic stresses. The tests were developed in the Laboratory of Experimental Germination and of the Experimental Forest Garden at the Universidade Estadual de Feira de Santana-BA. Experiments were carried out where the seeds were subjected to different temperatures and osmotic potential (Polyethyleneglycol 6000). Through the heat and osmotic screening could identify the point of priming and establish a protocol of priming for the species. For both the tests of germination in the laboratory and for each treatment were used 4 replicates of 25 seeds in petri dishes and moistened with distilled water or PEG 6000. For the field tests were used 4 replicates of 40 vases (50 cm high and 12.5 cm radius) with seeds primed and not primed. Thus, we observed the response of germination of primed seeds these when subjected to stresses, including comparing seeds of different ages. We conclude that Physalis angulata is a species that tolerates high temperatures and more severe water stress and that priming was effective in older seeds and seedlings from these.